Stem Cell Factor Gene Transfer Improves Cardiac Function After Myocardial Infarction in Swine. (January 2015) - Ishikawa, Kiyotake; Fish, Kenneth; Aguero, Jaume; Yaniz-Galende, Elisa; Jeong, Dongtak; Kho, Changwon; Tilemann, Lisa; Fish, Lauren; Liang, Lifan; Eltoukhy, Ahmed A.; Anderson, Daniel G.; Zsebo, Krisztina; et al.
<x xml:space="preserve">Abstract</x> Background— Stem cell factor (SCF), a ligand of the c-kit receptor, is a critical cytokine, which contributes to cell migration, proliferation, and survival. It has been shown that SCF expression increases after myocardial infarction (MI) and may be involved in cardiac repair. The aim of this study was to determine whether gene transfer of membrane-bound human SCF improves cardiac function in a large animal model of MI. Methods and Results— A transmural MI was created by implanting an embolic coil in the left anterior descending artery in Yorkshire pigs. One week after the MI, the pigs received direct intramyocardial injections of either a recombinant adenovirus encoding for SCF (Ad.SCF, n=9) or β-gal (Ad.β-gal, n=6) into the infarct border area. At 3 months post-MI, ejection fraction increased by 12% relative to baseline after Ad.SCF therapy, whereas it decreased by 4.2% (P=0.004) in pigs treated with Ad.β-gal. Preload-recruitable stroke work was significantly higher in pigs after SCF treatment (Ad.SCF, 55.5±11.6 mm Hg versus Ad.β-gal, 31.6±12.6 mm Hg, P=0.005), indicating enhanced cardiac function. Histological analyses confirmed the recruitment of c-kit+ cells as well as a reduced degree of apoptosis 1 week after Ad.SCF injection. In addition, increased capillary density compared with pigs treated with Ad.β-gal was found at 3 months and suggests an angiogenic role of SCF. Conclusions— Local overexpression of SCF post-MI induces the recruitment of c-kit+ cells at the infarct border area acutely. In the chronic stages, SCF gene transfer was associated with improved cardiac function in a preclinical model of ischemic cardiomyopathy.